2015
DOI: 10.1186/s13620-016-0065-6
|View full text |Cite
|
Sign up to set email alerts
|

A survey of rift valley fever and associated risk factors among the one-humped camel (Camelus dromedaries) in Sudan

Abstract: BackgroundRift valley fever (RVF) is a mosquito-borne viral disease of domestic livestock and wild ruminants. In camels RVF may cause abortion among pregnant camels, but is most often asymptomatic among other camels. In this study, a seroepidemiological survey was conducted to determine the prevalence of RVFV antibodies and to identify the potential risk factors associated with RVFV seropositivity among the Sudanese one-humped camel (Camelus dromedaries) in Khartoum State, Sudan. A cross sectional study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…This age group is considered the age of maturity or adulthood for camels when they are released into the pasture for grazing and travel long distances where they may be exposed to infected mosquitoes and other hematophagous insects and hence the high positivity among this age group. This agrees with some authors, who all reported higher risks of older camels to Rift Valley fever infection like [2223,32]. The camel owners give younger camels more attention and provide them with the necessary care which minimizes the risk of infectious diseases contraction like vector-borne diseases due to short distances covered.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This age group is considered the age of maturity or adulthood for camels when they are released into the pasture for grazing and travel long distances where they may be exposed to infected mosquitoes and other hematophagous insects and hence the high positivity among this age group. This agrees with some authors, who all reported higher risks of older camels to Rift Valley fever infection like [2223,32]. The camel owners give younger camels more attention and provide them with the necessary care which minimizes the risk of infectious diseases contraction like vector-borne diseases due to short distances covered.…”
Section: Discussionsupporting
confidence: 89%
“…It is a general observation that female animals stay longer than males in the herd. Therefore the longer the females stay in the herd, the longer they are exposed to risk factors associated with RVF [23]. This corroborates with the report by [41] in Mauritania and [40] in Tanzania regarding significant sero-positivity with female sex.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Abdalla et al . [63], when they evaluated the risk factors for RVFPV infection in Camels ( Camelus dromedaries ) in Sudan, and Blomström et al . [33], when investigated the seroprevalence of RVFPV in sheep and goats in Zambezia Province, obtained a similar result.…”
Section: Discussionmentioning
confidence: 99%
“…[33], when investigated the seroprevalence of RVFPV in sheep and goats in Zambezia Province, obtained a similar result. This is commonly seen in infectious diseases and for RVF it may be due to the longer exposure time of the adult animals in the herds, where they are in contact with potential mosquitoes vectors during several rain seasons, with increased risk of acquiring RVFPV infection through bites from infected mosquitoes [33,63]. Very little is known of the ecology of the mosquito vectors of RVFPV in Mozambique.…”
Section: Discussionmentioning
confidence: 99%